Pengaruh Struktur Kepemilikan dan Karakteristik Perusahaan Terhadap Transfer Pricing - Geulis Ari Maneges; Jarot Tri Bowo Santoso (Universitas Katolik Soegijapranata Semarang, 2026)
This study examines the effect of ownership structure and firm characteristics on the intensity of transfer pricing practices. Transfer pricing remains an important issue due to its potential misuse for profit shifting among affiliated entities to achieve tax efficiency. This issue has increasingly attracted the attention of regulators in Indonesia due to the risk of tax avoidance arising from such practices that may erode government tax revenue. This study uses unbalanced panel data from 820 non-financial companies listed on the Indonesia Stock Exchange during 2020-2024, resulting in 4.084 firm-year observations. The findings indicate that foreign ownership, profitability, leverage, and financial distress increase the intensity of transfer pricing practices, whereas institutional ownership does not show a significant relationship. These findings imply that companies facing higher financial pressure and certain ownership structures tend to have stronger incentives to engage in transfer pricing practices. Accordingly, tax regulators should strengthen monitoring of companies with higher risk indicators related to transfer pricing activities.